1997
DOI: 10.1016/s0735-1097(97)00063-6
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Reactivity Is Enhanced in Genetic Males Taking High Dose Estrogens

Abstract: Long-term treatment with high dose estrogens is associated with enhanced arterial reactivity in genetic males, which may be due to the effects of estrogen excess or androgen deprivation, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…These observations are similar to those of others 24 who failed to observe any changes in epicardial coronary flow in postmenopausal women with CAD after long-term administration of estrogen, but differ from those of others who reported favorable effects of long-term administration of estrogen on vascular reactivity of atherosclerotic coronary arteries in both humans 19,20,25 and subhuman primates. 26,27 These differences could be due to the different types of estrogens used in the different studies or the different methods used to elicit and measure vasomotor changes (ie, acetylcholine versus CPT).…”
Section: Campisi Et Al Estrogen Replacement and Myocardial Blood Flowsupporting
confidence: 89%
“…These observations are similar to those of others 24 who failed to observe any changes in epicardial coronary flow in postmenopausal women with CAD after long-term administration of estrogen, but differ from those of others who reported favorable effects of long-term administration of estrogen on vascular reactivity of atherosclerotic coronary arteries in both humans 19,20,25 and subhuman primates. 26,27 These differences could be due to the different types of estrogens used in the different studies or the different methods used to elicit and measure vasomotor changes (ie, acetylcholine versus CPT).…”
Section: Campisi Et Al Estrogen Replacement and Myocardial Blood Flowsupporting
confidence: 89%
“…21 Furthermore, studies in male-to-female transsexuals have shown that both flow-mediated and nitroglycerininduced vasodilations in the brachial artery are enhanced compared with control men, suggesting that high-dose estrogen treatment enhances vascular reactivity in genetic males. 22,23 In healthy young men, single doses of sublingual estradiol or intravenous conjugated equine estrogens, at plasma concentrations within the physiological range for premenopausal women, have been shown to induce rapid onset, rapid offset, nongenomic effects on the endotheliummediated vasodilator response to acetylcholine, with no effect on the endothelium-independent action of sodium nitroprusside. 24 Not all studies have yielded positive results: for example, a study of short-term estrogen supplementation failed to show an effect on acetylcholine-induced coronary artery vasoconstriction in men, 25 and estrogens reportedly did not augment flow-mediated dilation in the brachial artery or influence serum levels of metabolites of NO in older male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low circulating levels of estrogen found in men, a physiologic role for ER ␣ in males is supported by both animal and human studies. For example, estrogen administration improves vascular reactivity in some men (34)(35)(36), inhibits the response to carotid injury in castrated male rats (37), and reduces plaque formation in transgenic male mice which express high levels of apoE (38). Furthermore, disruption of the ER ␣ gene leads to an abnormal phenotype in male mice that includes both abnormal behavior and sterility (39-42).…”
Section: Introductionmentioning
confidence: 99%